Mobility challenges and transport safety of people with disabilities (PWDs) in Ibadan, Nigeria (2015)
Disability is a growing problem worldwide. The challenges facing people with disabilities are being exacerbated by poor and inadequate transport. This paper assessed the mobility challenges and transport safety of disabled people in Ibadan Metropolis. Data were collected from both primary and secondary sources. A structured questionnaire was administered on 388 respondents (crippled and blind) in 2 major motor parks, designated bus stops and road terminals along corridors where people with disabilities are concentrated. Secondary information was sourced from the disabled homes in the state. Descriptive and inferential statistics were used for data analysis. Findings indicated that about 2/3 were male, 72% had no more than primary education and begging was the main source of income. About 90% made only two trips per day, more than 65% spent more than 10 minutes at bus stops and 80% relied on public transport. Road environment and vehicle design were the main mobility challenges and about a half were victims of road crashes. Significant correlation existed among number of trips, sex, educational attainment and income. The paper suggested accessible transport infrastructure, disability awareness training for public transport staff, improved vehicle design and disable-oriented mobility planning in order to meet the access needs of people with disabilities.